Poverty in education across the UK : a comparative analysis of policy and place - Thompson, Ian; Ivinson, Gabrielle; Dorling, Danny (Bristol : Policy Press, 2020)
Nuanced interconnections of poverty and educational attainment around the UK are surveyed in this unique analysis. Across the four jurisdictions of England, Scotland, Wales and Northern Ireland, experts consider the impact of curriculum reforms and devolved policy making on the lives of children and young people in poverty. They investigate differences in educational ideologies and structures, and question whether they help or hinder schools seeking to support disadvantaged and marginalised groups. For academics and students engaged in education and social justice, this is a vital exploration of poverty's profound effects on inequalities in educational attainment and the opportunities to improve school responses.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: Children with social disabilities -- Education -- Great Britain; Poverty -- Great Britain